Involuntary Capture and Voluntary Reorienting of Attention Decline in Middle-Aged and Old Participants - Correa-Jaraba, Kenia S.; Cid-Fernández, Susana; Lindín, Mónica; Díaz, Fernando (Frontiers in Human Neuroscience, 2016)
The main aim of this study was to examine the effects of aging on event-related brain potentials (ERPs) associated with the automatic detection of unattended infrequent deviant and novel auditory stimuli (Mismatch Negativity, MMN) and with the orienting to these stimuli (P3a component), as well as the effects on ERPs associated with reorienting to relevant visual stimuli (Reorienting Negativity, RON). Participants were divided into three age groups: (1) Young: 21-29 years old; (2) Middle-aged: 51-64 years old; and (3) Old: 65–84 years old. They performed an auditory-visual distraction-attention task in which they were asked to attend to visual stimuli (Go, NoGo) and to ignore auditory stimuli (S: standard, D: deviant, N: novel). Reaction times (RTs) to Go visual stimuli were longer in old and middle-aged than in young participants. In addition, in all three age groups, longer RTs were found when Go visual stimuli were preceded by novel relative to deviant and standard auditory stimuli, indicating a distraction effect provoked by novel stimuli. ERP components were identified in the Novel minus Standard (N-S) and Deviant minus Standard (D-S) difference waveforms. In the N-S condition, MMN latency was significantly longer in middle-aged and old participants than in young participants, indicating a slowing of automatic detection of changes. The following results were observed in both difference waveforms: (1) the P3a component comprised two consecutive phases in all three age groups - an early-P3a (e-P3a) that may reflect the orienting response towards the irrelevant stimulation and a late-P3a (l-P3a) that may be a correlate of subsequent evaluation of the infrequent unexpected novel or deviant stimuli; (2) the e-P3a, l-P3a and RON latencies were significantly longer in the Middle-aged and Old groups than in the Young group, indicating delay in the orienting response to and the subsequent evaluation of unattended auditory stimuli, and in the reorienting of attention to relevant (Go) visual stimuli, respectively; and (3) a significantly smaller e-P3a amplitude in Middle-aged and Old groups, indicating a deficit in the orienting response to irrelevant novel and deviant auditory stimuli.